Kontribusi Daya Ledak Lengan, Kelincahan, dan Koordinasi Mata Tangan terhadap Keterampilan Bermain Bola Voli Siswa SMP Negeri 34 Makassar - Andi Rizal; Masjumi Nur (Seminar Nasional LP2M UNM, 2019)
This research is a descriptive research that aims to determine the contribution of arm explosive power, agility and hand eye coordination to the playing skills of Volleyball Students at 34 State Junior High School Makassar, using a sample of 30 male students who were randomly obtained. Furthermore, data collection for each variable is carried out, in this study using the two hand medicine ball put test, the agility test (shuttle run test), and the coordination test, and playing skills test Volleyball which is standard. Processing and data analysis using regression analysis. Based on the results of the data analysis, the following research conclusions are obtained: (1) There is a linear and significant contribution to the explosive power of the arms to the playing skills of the Volleyball Students SMP 34 Makassar, amounting to 40.50%. (2) There is a linear and significant contribution of agility to the playing skills of Volleyball Students SMP 34 Makassar 34 amounting to 56.20%. (3) There is a linear and significant contribution of hand eye coordination to the volleyball playing skills of State Junior High School 34 Makassar students, amounting to 78.70% (4) There is a linear and significant contribution to the combination of arm explosive power, agility and hand eye coordination to the playing skills of Volleyball Junior High School Students Negeri 34 Makassar, amounting to 80.90%.